External tariff liberalization in CARICOM : a commodity-level analysis - Sadikov, Azim (IMF [Washington]US, 2008)
Estimates the impact of the tariff liberalization in Barbados, Guyana, Jamaica and Trinidad and Tobago on their trade flows.